Penerapan TQM dan Kinerja Inovasi terhadap Kinerja Manajerial Industri Rokok Kabupaten Kudus - Sri Mulyani; Dianing Ratna Wijayani (Universitas Swadaya Gunung Jati, 2017)
AbstractThe national cigarette industry contributes Rp 90 trillion per year. Total Quality Management (TQM) used to maximize the existence of organizational competition through continuous improvement, products and services. This research is an empirical research using quantitative method, whose purpose is for hypothetical choice related to the influence of interaction between total quality management implementation, organizational commitment, local culture, and innovation performance on managerial performance in cigarette industry in Kudus. This study was conducted with primary data through the distribution of questionnaires using purposive sampling method. This study uses the respondent is the production manager in the cigarette industry in Kudus District with a sample of 44 respondents. The results of this study indicate 1) TQM implementation has positive effect on managerial performance, 2) Interaction of TQM implementation with organizational commitment has not effect on managerial performance, 3) Interaction of TQM implementation with environmental uncertainty not biased on managerial performance, 4) Interaction of TQM implementation and culture local has positive effect on managerial performance, and 5) Interaction of TQM implementation which mediated by innovation performance has effect on managerial performance. Keywords: Local culture